Development of school mathematical education of the Republic Kazakhstan under conditions of realization of competence approach - T O Balykbayev; T A Aldibayeva (RUDN Journal of Informatization in Education, 2011)
Purposes, tasks, expected results, basic content of school mathematical education of the Republic of Kazakhstan under conditions of realization of competency approach were considered in the article